Монетарный механизм развития экономики ЕС - Вишневский, В.П.; Матюшин, А.В.; Вишневская, Е.Н. (Економіка промисловості, 2015)
Проанализированы современные особенности монетарного механизма развития экономики ЕС и ожидаемые эффекты его функционирования с учѐтом новых экономических, институциональных и геополитических обстоятельств развития, обусловленных, в частности, мировым финансовым кризисом 2007-2008 гг., долговым кризисом в Европе. Определены возможности адаптации европейского опыта для решения новых задач, которые стоят перед экономикой Украины в целом и еѐ промышленностью в частности на современном этапе развития. Проаналізовано сучасні особливості монетарного механізму розвитку економіки ЄС та очікувані ефекти його функціонування з урахуванням нових економічних, інституційних і геополітичних обставин розвитку, обумовлених, зокрема, світовою фінансовою кризою 2007-2008 рр., борговою кризою у Європі. Визначено можливості адаптації європейського досвіду для вирішення нових завдань, які стоять перед економікою України у цілому і її промисловістю зокрема на сучасному етапі розвитку. The paper deals with the features of modern monetary mechanism of the EU economy and the expected effects of its operation taking into account the new economic, institutional and geopolitical circumstances, in particular, the global financial crisis of 2007-2008, the debt crisis in Europe, the possibility of adapting the European experience to meet the new challenges facing the economy of Ukraine in general and its industry, in particular, at the present stage of development. It is concluded that the combination of a few countries in the single currency area has not only the positive effects associated with the convergence of national economies, transaction costs reducing and the unity of monetary policy, but also negative ones because of the different levels of development of political, economic, monetary and fiscal systems of members countries and their institutional characteristics, and as a consequence - the financial fragmentation of EMU, when individuals and legal entities with the same profile working and operating in different countries get different access to financial resources and on different terms. To overcome the effects of the crisis both on the side of national governments of the euro zone countries and on the side of ECB the measures have been taken to stimulate business activity, improve sovereign and bank balance sheets. In particular, the ECB has pursued a policy of reducing the refinancing rates on loans and deposits, credit and quantitative easing by the ECB's purchase of commercial papers, corporate bonds and securities backed by assets, long-term government commitments from commercial banks and other private enterprises. Interest rates on deposits of the major central banks have been reduced to negative values for the first time in recent history. In sum it has allowed, though not immediately, to stabilize the situation and get out on the path of economic growth, prospects of which for the coming years are estimated to be moderately optimistic. The current situation in the euro area is characterized by the gradual improvement of the rational expectations of economic agents. However, the economic recovery is still insufficient and uneven. Inflation is too low for too long, financial markets still remain fragmented. This situation prevents the sustainable recovery of economic equilibrium and substantial progress in reducing debt and unemployment.